2012
DOI: 10.1159/000338635
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structure in Preclinical Huntington's Disease: A Multi-Method Approach

Abstract: Background: Structural magnetic resonance imaging (MRI) of the brain could be a powerful tool for discovering early biomarkers in clinically presymptomatic carriers of the Huntington's disease gene mutation (preHD). So far, structural changes have been found mainly in preHD approaching the estimated motor onset of the disease (i.e. less than 15 years from onset), whereas structural findings in preHD far from the estimated motor onset have been inconclusive. Objectives: The aims of this study were to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 60 publications
(114 reference statements)
2
25
0
Order By: Relevance
“…Given that the disease burden score in our cohort was substantially lower than in other cohorts (e.g. refs 14, 15, 16, 17) people with far from onset preHD may develop structural changes when they get nearer to manifesting diagnostic signs of clinically manifest HD. This suggests that, at least with the methods we used, the structural changes ascribed to the pathogenesis of HD may not be evident far from motor onset.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Given that the disease burden score in our cohort was substantially lower than in other cohorts (e.g. refs 14, 15, 16, 17) people with far from onset preHD may develop structural changes when they get nearer to manifesting diagnostic signs of clinically manifest HD. This suggests that, at least with the methods we used, the structural changes ascribed to the pathogenesis of HD may not be evident far from motor onset.…”
Section: Discussionmentioning
confidence: 59%
“…refs 14, 15, 16, 17). In agreement with many studies, we found no clinically meaningful motor signs, and cognitive task performance was similar to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2010; Wolf et al. 2013), most studies report no relationship between cortical volume loss or thinning and cognition (Novak et al. 2012; Wolf et al.…”
Section: Discussionmentioning
confidence: 99%
“…Yet a recent study of 20 prHD individuals found no statistically significant relationships between cortical morphometry and cognitive functioning on tests of alertness, divided attention, verbal and spatial working memory, inhibition, or executive dysfunction (Wisconsin Card Sorting Test, WCST), irrespective of the structural magnetic resonance imaging (sMRI) method employed (i.e., VBM and cortical surface modeling) (Wolf et al. 2013). These discrepant findings may relate to the small sample sizes, which is problematic given the heterogeneity of symptoms and disease progression in prHD.…”
Section: Introductionmentioning
confidence: 99%